2004
DOI: 10.1158/0008-5472.can-03-3924
|View full text |Cite
|
Sign up to set email alerts
|

Transactivation of the PPAR-Responsive Enhancer Module in Chemopreventive Glutathione S -Transferase Gene by the Peroxisome Proliferator-Activated Receptor-γ and Retinoid X Receptor Heterodimer

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 53 publications
5
106
1
Order By: Relevance
“…This indicates that PPARg could act on upstream signal pathways for Nrf2 activation. In support of this function, accumulating evidence has indicated that PPARg agonists induce antioxidant and defense genes encoding GST-a, HO-1, and CD36 through regulation of Nrf2 (43)(44)(45). The current study also supported this concept, first by showing suppressed Nrf2 expression and ARE binding activity after PPARg silencing, and then by elucidating potential PPAR binding motifs in the Nrf2 promoter.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This indicates that PPARg could act on upstream signal pathways for Nrf2 activation. In support of this function, accumulating evidence has indicated that PPARg agonists induce antioxidant and defense genes encoding GST-a, HO-1, and CD36 through regulation of Nrf2 (43)(44)(45). The current study also supported this concept, first by showing suppressed Nrf2 expression and ARE binding activity after PPARg silencing, and then by elucidating potential PPAR binding motifs in the Nrf2 promoter.…”
Section: Discussionsupporting
confidence: 75%
“…Recent studies indicate that PPARg may control the expression of cytoprotective genes including GST-a, HO-1, and CD36 directly through their PPRE or indirectly through Nrf2 (41)(42)(43)(44)(45). To determine whether PPARg modulates these cytoprotective genes and Nrf2 in the lung, their expression was compared in wild type mice treated with si-PPARg or si-NS ( Figure 7A).…”
Section: Effect Of Pparg Inhibition On Cytoprotective Genes and Nrf2mentioning
confidence: 99%
“…Moreover, it has been shown that the Gsta2 expression is transcriptionally regulated by NRF2 and C/EBP . In addition, functional multiple PPRE-responsive enhancer module (PPREM) was recently reported in the Gsta2 promoter, by which PPAR agonists induce the Gsta2 expression via PPREM in hepatocytes 59) . Therefore, the mechanism underlying the reduction of the Gsta2 expression induced by K-877 treatment in Ppara-null…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Also, PPAR-gamma agonists trans-repress the transcription of downstream pro-inflammatory genes after ischemia (37) (Table 3). Furthermore, the administration of rosiglitazone or pioglitazone increases the translocation of PPAR-gamma to the nucleus in neurons and this is further enhanced in the presence of retinoic acid (37,38). Freshly prepared peripheral blood monocytes treated with TZDs showed decreased cytokine release after activation and 15d-PGJ2 modified target gene expression changes when administered to peritoneal macrophages (20,85).…”
Section: Ppar-gamma and Focal Cerebral Ischemiamentioning
confidence: 99%